Chemical vapour deposition (CVD) of nickel oxide using the novel nickel dialkylaminoalkoxide precursor [Ni(dmamp′)2] (dmamp′ = 2-dimethylamino-2-methyl-1-propanolate). Issue 36 (23rd June 2021) - Wilson, Rachel L.; Macdonald, Thomas J.; Lin, Chieh-Ting; Xu, Shengda; Taylor, Alaric; Knapp, Caroline E.; Guldin, Stefan; McLachlan, Martyn A.; Carmalt, Claire J.; Blackman, Chris S.
Abstract : We describe CVD of nickel oxide (NiO) thin films using a new precursor [Ni(dmamp′)2 ], synthesised using a readily commercially available dialkylaminoalkoxide ligand (dmamp′), which is applied to synthesis of a hole transport-electron blocking layer. Abstract : Nickel oxide (NiO) has good optical transparency and wide band-gap, and due to the particular alignment of valence and conduction band energies with typical current collector materials has been used in solar cells as an efficient hole transport-electron blocking layer, where it is most commonly deposited via sol–gel or directly deposited as nanoparticles. An attractive alternative approach is via vapour deposition. This paper describes the chemical vapour deposition of p-type nickel oxide (NiO) thin films using the new nickel CVD precursor [Ni(dmamp′)2 ], which unlike previous examples in literature is synthesised using the readily commercially available dialkylaminoalkoxide ligand dmamp′ (2-dimethylamino-2-methyl-1-propanolate). The use of vapour deposited NiO as a blocking layer in a solar-cell device is presented, including benchmarking of performance and potential routes to improving performance to viable levels.